Communication Skills in Athletes - Uluöz, Togay (2019)
The aim of this study is to find out the different level of communication skills between  volleyball, handball, basketball athletes. Near East University Athletes Development Club athletes’ participated in this study. The data collected from 60 athletes in the teams of volleyball (17), handball (24) and basketball (19) in 2018-2019. 38.33% of the participants were 19 years of age and 23.33% were between the ages of 20-22, 38.33% were aged 23 and over. Moreover, 51.67% were women and 48.33% were male. Frequency distribution in data analysis, t-test for comparison of two groups and ANOVA analysis of variance to determine the relationship between more than two variables, chi square, standard deviation, the fit of the data set to normal distribution, Shapiro-Wilk test, QQ plot graph and distribution-related skewness-kurtosis coefficients were examined. Levene techniques were applied for homogeneity of variances. The difference between the views of the groups was interpreted by taking into account the P <0.05 significance level. According to the results; there was no significant difference between the mean scores of the communication skills scale at the level of P <0.05 when the athletes were examined in terms of age and sports barriers, but the difference between the points they got from the behavioral sub-dimension in communication skills inventory was statistically significant. In conclusion, it has been found that sports have a positive effect on the communication skills of athletes.